KONSEP KESADARAN GENDER DALAM PENDIDIKAN ISLAM: TELAAH BUKU THE TAO OF ISLAM KARYA SACHIKO MURATA - Nur Amanah; Nesia Andriana; Imas Kania Rahman (Kuttab : Jurnal Ilmu Pendidikan Islam, 2023)
Gender awareness is a crucial ability taught in Islamic education to ensure that students accurately comprehend their responsibilities as Muslims. The current issue is that the concept of gender has been co-opted by Western ideology, resulting in Muslims having a negative opinion of their religion. This study looks at gender awareness education in Sachiko Murata's book The Tao of Islam. Utilizing a library research method, this study discovered that, according to cosmological theory, everything in God's cosmos was formed in pairs. Gender and gender are as inextricably linked as the sky, and the earth was created to affect the individual responsibilities, rights, and obligations of each according to Islamic teachings.